Overcoming the Challenge: Assessing Reading and Writing Literacy in Fourth-Grade Students - Rediani, Ni Nyoman; Kaize, Bernadetha Risky; Nainggolan, Herrio Tekdi (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The research aims to assess fourth-grade students' reading and writing literacy. Understanding the literacy level in this age group is crucial for identifying areas requiring improvement and enhancing their skills. This study provides insights for educational enhancements. Methodology: The research utilized a quantitative descriptive research design involving 85 fourth-grade students as participants. Data collection methods included interviews, observations, and tests. The interactive data analysis model was applied, consisting of three essential stages: data reduction, data presentation, and concluding (verification). Main Findings: The findings from this study highlight a prevailing issue concerning the reading and writing literacy skills of students, indicating that the majority of students, over 55%, are categorized as having